Data from: Temporal variation in the vocal behaviour of southern right whales in the Auckland Islands, New Zealand ... - Webster, Trudi; Van Parijs, Sofie; Rayment, Will; Dawson, Steve (Dryad, 2019)
Autonomous recorders are frequently utilised for examining vocal behaviour of animals, and are particularly effective in remote habitats. Southern right whales are known to have an extensive acoustic repertoire. A recorder was moored at the isolated sub-Antarctic Auckland Islands for a year to examine whether the acoustic behaviour of southern right whales differed seasonally and throughout the day at their main calving ground in New Zealand. Recordings were made in each month except June, and vocalisations were audible in all months with recordings except January. A total of 35,487 calls were detected, of which upcalls were the most common (11,623). Call rate peaked in August (288±5.9 [SE] calls/hour) and July (194±8.3). Vocal behaviour varied diurnally with highest call rates detected at dusk and night, consistent with the concept that upcalls function primarily as contact calls. Zero-inflated model results confirmed that seasonal variation was the most important factor for explaining differences in vocal ... : Summary of the analysis of the southern right whale vocalisation dataThis spreadsheet contains data on the presence of right whale vocalisations for all of the recordings from the DSG recorder. Subsequent tabs in the spreadsheet contain the analysis of calls by season, month, per day, diel period and hour and call typeDSGAnalysisSummary.xlsxSummary of the detector performance dataThis spreadsheet contains data on the performance of the automated detector (the eXtensible BioAcoustic Tool (XBAT) written in MATLAB) which was developed for upcall vocalisations produced by North Atlantic right whales. Manual and automated detections were compared to test the effectiveness and sensitivity of the algorithm for detecting SRW upcalls. We randomly selected 10% of the total number of recordings for verification analysis and annotated the detection events as either true or false based on the manual classification. Two measures of detector performance were applied: Positive Predictive Value (PPV) which represents the ...